Análise numérica de blocos sobre duas estacas com variações das seções dos pilares, das rigidezes dos blocos e taxas de armaduras dos pilares - Resende, Jéssica Cunha (2019)
The strut and tie method is capable of closely representing the structural behavior of pile caps. However, there is no exact criterion for determining the cross sections of the struts of some elements, especially in pile caps. Thus, this work aims to analyze the structural behavior of reinforced concrete pile caps containing two piles, under a centered load, with variation of the following parameters: cross section and reinforcement ratio of the columns and pile cap stiffness. For this, twenty-seven models were defined, later modeled with ANSYS software for numerical analysis using the Finite Element Method. The models were designed and detailed based on the findings of Blévot and Frémy (1967) and the Brazilian code NBR 6118 (ABNT, 2014). In order to guarantee reliability to the software results, the model of Munhoz (2014) was processed and the parameters found in the models of this work were applied. Therefore, with the obtained results, comparisons were made between the models, evaluating factors such as: nodal tensions, compression struts, load-displacement curves and reinforcement stresses. Also, a variance analysis was performed, verifying the relevance of the considered parameters, being the cross section of the columns, followed by the height of the caps, fundamental factors in the structural behavior of the pile caps.